Manifestations of Religion or Belief in the Case Law of the European Court of Human Rights - Martínez-Torrón, Javier (Religion and human rights, 2017)
This article analyses the case law of the European Courts of Human Rights on manifestation of religion or belief under Article 9 echr, excluding particular types of manifestation that are covered in other articles in this special issue. It provides an overview of the main holdings of the Court in this area, together with some critical comments about aspects of the Court’s case law that, in the author’s view, should be improved.